2019
DOI: 10.2147/ijwh.s216608
|View full text |Cite
|
Sign up to set email alerts
|

<p>Domestic violence and its association with pre-term or low birthweight delivery in Vietnam</p>

Abstract: ObjectiveTo examine the association between various types of domestic violence (DV) during pregnancy (emotional violence, physical violence, and sexual violence) and pre-term or low birthweight delivery in women living in Ho Chi Minh city, Vietnam.MethodsA cross-sectional study was conducted in ten districts of Ho Chi Minh city during the period of January 1, 2015–July 4, 2016, with 1,099 women aged 18–49 years old who had delivered at least one child within the past 2years and were living in Ho Chi Minh city.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 16 publications
1
9
2
1
Order By: Relevance
“…A recent national study examining violence against women in Vietnam found a similar prevalence of physical p-IPV (3.4%) [62]. However, this prevalence was lower than the findings of studies with Vietnamese mothers in our recent review (30% for emotional p-IPV and 5% for physical IPV) [22] and lower than the prevalence among women in a survey in northern Vietnam (35.3%) [26] and among female patients seeking fertility treatment in a southern city (16.8% for emotional violence, 7.3% for physical violence, and 12.4% for sexual violence) [63]. This difference might reflect the significant influence of Buddhist values of kindness, belief in karma, nonviolence and Nirvana (the state of peace and happiness, achieved after giving up three poisons of greed, hatred, and delusion), which are especially strong in the contemporary population of Hue City [64].…”
Section: Discussioncontrasting
confidence: 75%
“…A recent national study examining violence against women in Vietnam found a similar prevalence of physical p-IPV (3.4%) [62]. However, this prevalence was lower than the findings of studies with Vietnamese mothers in our recent review (30% for emotional p-IPV and 5% for physical IPV) [22] and lower than the prevalence among women in a survey in northern Vietnam (35.3%) [26] and among female patients seeking fertility treatment in a southern city (16.8% for emotional violence, 7.3% for physical violence, and 12.4% for sexual violence) [63]. This difference might reflect the significant influence of Buddhist values of kindness, belief in karma, nonviolence and Nirvana (the state of peace and happiness, achieved after giving up three poisons of greed, hatred, and delusion), which are especially strong in the contemporary population of Hue City [64].…”
Section: Discussioncontrasting
confidence: 75%
“…O rastreamento da violência doméstica na gestação durante o pré-natal é o principal meio de intervenção desse problema de saúde. Assim que detectada, as gestantes devem receber toda assistência de aconselhamento e ser encaminhada a programas locais responsáveis e habilitados para assistir a gestante, obtendo assim êxito nas intervenções (Carneiro, et al, 2016, Vo, et al, 2019. & Silva & Leite, 2020.…”
Section: Discussionunclassified
“…Regarding an inter-generational effect, children from women who experience p-IPV tend to struggle with various physical and social problems from early infancy such as low birth weight (LBW), pre-term birth (PTB) (Hoang et al, 2016;Vo et al, 2019), and have delayed social-emotional development (Tran et al, 2014). However, considerable knowledge gaps remain in Vietnam and other LMIC to determine which risk factors are causal at the macro level in which contexts, and how these can be effectively prevented to reduce violence against women (Brown et al, 2020).…”
Section: Context Looking Through the Lens Of The Vietnamese Contextmentioning
confidence: 99%
“…The seminal research by Fisher and her colleagues has been extended by Tran et al (2014) with many publications on maternal mental disorders and their impact on early childhood cognitive development. Some recent studies on p-IPV in Vietnam have also examined p-IPV prevalence and correlated maternal mental health during pregnancy (Mai et al, 2020), PPD (Murray et al, 2015;Ngo et al, 2018;Nguyen et al, 2015;Tran et al, 2018d;Vo et al, 2019;Vo et al, 2017), birth outcomes (Hoang et al, 2016;Ngo et al, 2018;Vo et al, 2019), and socioeconomic welfare for children (Bui et al, 2018). Some studies have focused on the key predictors of p-IPV in Vietnam, such as husband's role (Nguyen et al, 2020a), social support (Nguyen et al, 2018b), and health care systems response to domestic violence (Bui et al, 2010;Le et al, 2019).…”
Section: Context Looking Through the Lens Of The Vietnamese Contextmentioning
confidence: 99%
See 1 more Smart Citation